Assessment of the safe and efficacious dose of the selective progesterone receptor modulator vilaprisan for the treatment of patients with uterine fibroids by exposure–response modelling and simulation. Issue 2 (25th August 2021) - Sutter, Gabriele; Frei, Matthias; Schultze‐Mosgau, Marcus‐Hillert; Petersdorf, Kathrin; Seitz, Christian; Ploeger, Bart A.
Abstract : Aims: We report population pharmacokinetic (popPK) and exposure–response (E–R) analyses for efficacy (induced amenorrhoea [IA]) and safety (unbound oestradiol [E2] concentrations) of the selective progesterone receptor modulator vilaprisan. Results were used to inform the dose for the Phase 3 programme in patients with uterine fibroids. Methods: A popPK model was developed using data from Phase 1 and 2 studies (including ASTEROID 1 and 2). The relationship between vilaprisan exposure (steady‐state AUC) and IA after oral administration of 0.5, 1, 2 or 4 mg/day over 3 months was analysed in ASTEROID 1 using logistic regression and qualified in ASTEROID 2 by comparing simulated and observed probability for IA after 2 mg/day. The exposure–E2 relationship was analysed visually. Results: Vilaprisan clearance was 22.7% lower in obese vs non‐obese patients. The E–R relationship for IA in ASTEROID 1 was steep and consistent with ASTEROID 2, with a maximum probability ( P max ) of 59% (95% CI: 49–68%). The exposure at which 50% of P max is obtained was 36.9 μg*h/L (95% CI: 27.7–48.7 μg*h/L). Simulations showed that 36% of the patients will be below 90% of P max for IA after 1 mg/day compared to 2% after 2 mg/day. E2 levels tended to decrease with increasing exposure. While E2 levels remained largely within the physiologic follicular phase range, the clinical relevance of this decrease will be evaluated in long‐term studies. Conclusions: A 2 mg/day dose was selected for Phase 3 as E–R analyses show this dose results in a close to maximum probability for IA, without any safety concerns noted.